KEWENANGAN DIREKTORAT KEPOLISIAN PERAIRAN DAN UDARA POLDA LAMPUNG DALAM PENYIDIKAN TINDAK PIDANA NARKOTIKA - Rangga Yoga Winata; Fathur Rachman; Yudi Yusnandi (VIVA THEMIS, 2022)
Authority is the right to do something or order other people to do or not do something in order to achieve certain goals, one of which is the authority exercised by the Directorate of Water and Air Police of the Lampung Regional Police in the context of eradicating narcotics crimes that violate Law Number 35 of 2009 concerning Narcotics with the formulation of the problem: a) What is the Authority of the Directorate of Water and Air Police of the Lampung Regional Police in Investigating Criminal Acts of methamphetamine-type Narcotics in the Coastal Area of Teladas Tulang Bawang Village?; b) Does BPOM Lampung have the authority to test laboratories in investigating criminal acts of methamphetamine-type narcotics in the coastal area of Teladas Tulang Bawang village?The research method used is through a normative approach and an empirical approach. Sources of data are primary data in the form of information obtained directly and secondary data. Data collection procedures through library research, review of laws, and field studies through interviews. the data used is descriptive qualitative.The results of research conducted on the basis of the authority of the Directorate of Water and Air Police of the Lampung Regional Police regarding narcotics in Teladas Village were carried out through a) 1. Investigation; 2. Title of Case and Delivery of Warrant for Commencement of Investigation (SPDP); 4. Forced Efforts; 5. Examination; 6. Settlement of Case Files; 7. Submission of Case Files to the Public Prosecutor; 8. Submission of Suspects and Evidence. b) The Lampung Food and Drug Supervisory Agency has the authority to carry out narcotics laboratory tests in accordance with the Drug and Food Control Agency Regulation Number 9 of 2020 concerning the Strategic Plan of the Food and Drug Supervisory Agency by cooperating with law enforcement, namely laboratory testing in accordance with the noble values of teamwork for the sake of To improve the quality of enforcement, BPOM must cooperate with law enforcement.